Specific Elements of Team-Based Learning Used in Nursing Education: A Scoping Review. Issue 5 (12th September 2021) - Considine, Julie; Berry, Debra; Allen, Joshua; Hewitt, Nicky; Oldland, Elizabeth; Sprogis, Stephanie K.; Currey, Judy
Abstract : Supplemental digital content is available in the text. Abstract : Background: Team-based learning (TBL) is an evidence-based, highly structured teaching strategy. Purpose: The purpose of this review was to explore the specific TBL structure and process design elements reported in nursing education studies. Methods: A scoping review was undertaken according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews. Databases were searched on February 15, 2021, using search terms related to nursing, education, and TBL. Results: Of 226 potentially relevant citations, 45 studies were included. The specific TBL design elements reported were team size (n = 41), team formation (n = 24), readiness assurance process (n = 45), immediate feedback (n = 42), activity sequencing (n = 42), 4S application design (n = 13), incentive structure(s) (n = 22), and peer evaluation (n = 13). Conclusions: There was variability in the reporting of TBL design elements. Preclass preparation and individual and team Readiness Assurance Tests were well reported. Application exercise design and approach to peer evaluation were gaps in the included studies.